Organocatalytic cycloaddition of alkynylindoles with azonaphthalenes for atroposelective construction of indole-based biaryls - Yang, Hui; Sun, Huai-Ri; He, Rui-Qing; Yu, Le; Hu, Wei; Chen, Jie; Yang, Sen; Zhang, Gong-Gu; Zhou, Ling (Nature communications, 2022)
The axially chiral indole-aryl motifs are present in natural products and biologically active compounds as well as in chiral ligands. Atroposelective indole formation is an efficient method to construct indole-based biaryls. We report herein the result of a chiral phosphoric acid catalyzed asymmetric cycloaddition of 3-alkynylindoles with azonaphthalenes. A class of indole-based biaryls were prepared efficiently with excellent yields and enantioselectivities (up to 98% yield, 99% ee). Control experiment and DFT calculations illustrate a possible mechanism in which the reaction proceeds via a dearomatization of indole to generate an allene-iminium intermediate, followed by an intramolecular aza-Michael addition. This approach provides a convergent synthetic strategy for enantioselective construction of axially chiral heterobiaryl backbones. There is great interest in methods for catalytic enantioselective construction of axially chiral compounds found in natural products. Here, the authors develop a cycloaddition strategy for atroposelective construction of indole-based biaryls via chiral phosphoric acid-catalysed cycloaddition.